The Effect of Academic Motivation on Academic Procrastination Among Undergraduate Students in Malaysia (Sains Humanika, 2025)
Academic procrastination is postponing academic tasks until feeling anxious to complete the tasks. It is believed that academic procrastination has been a common issue among students. Additionally, academic motivation is believed to be a crucial factor that determines the level of procrastination in academic matters. Therefore, this research aims to identify the effect of academic motivation on the academic procrastination in Malaysia Higher Educational Institutions. A total of 284 undergraduate students from Malaysia public and private universities were involved in this research. This research uses quantitative research design, which involves cross-sectional and correlational design. Academic Motivation Scale (AMS-C 28) and Procrastination Assessment Scale for Students (PASS) was used to measure academic motivation as independent variable and academic procrastination as dependent variable. Pearson correlation and multiple regression analysis were used to examine the relationship and effect. Findings from this research reveal that the undergraduate students have moderate level of academic procrastination. The findings also suggested that amotivation has a positive significant effect on academic procrastination. The research findings provide a reference to future researchers and implication to society that academic motivation is important to students. Overall, further investigation on this topic was encouraged.
Keywords: Academic motivation, academic procrastination, undergraduates.